2021
DOI: 10.1007/s12298-021-01096-x
|View full text |Cite
|
Sign up to set email alerts
|

microRNA 166: an evolutionarily conserved stress biomarker in land plants targeting HD-ZIP family

Abstract: MicroRNAs (miRNAs) are significant class of noncoding RNAs having analytical investigating and modulatory roles in various signaling mechanisms in plants related to growth, development and environmental stress. Conserved miRNAs are an affirmation of land plants evolution and adaptation. They are a proof of indispensable roles of endogenous gene modulators that mediate plant survival on land. Out of such conserved miRNA families, is one core miRNA known as miR166 that is highly conserved among land plants. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 104 publications
(97 reference statements)
1
18
0
Order By: Relevance
“…Thus, miR166 family members are highly conserved across diverse plant species, especially along the 3′ arm ( Barik et al, 2014 ). Mature miR166 members are known to regulate the abundance of transcripts encoding HD-ZIP III transcription factors in many species ( Boualem et al, 2008 ; Li R. et al, 2018 ; Yadav et al, 2021 ). In this study, we predicted that all Vco-miR166s derived from the 3′ arm target HD-ZIP III transcripts, supporting the functional conservation of miR166 family members in various species ( Supplementary Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, miR166 family members are highly conserved across diverse plant species, especially along the 3′ arm ( Barik et al, 2014 ). Mature miR166 members are known to regulate the abundance of transcripts encoding HD-ZIP III transcription factors in many species ( Boualem et al, 2008 ; Li R. et al, 2018 ; Yadav et al, 2021 ). In this study, we predicted that all Vco-miR166s derived from the 3′ arm target HD-ZIP III transcripts, supporting the functional conservation of miR166 family members in various species ( Supplementary Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, miR166 is a highly conserved miRNA implicated in a wide range of cellular and physiological processes by regulating its cognate target genes encoding members from the homeodomain leucine zipper (HD-ZIP III) family of transcription factors ( Miyashima et al, 2013 ; Singh et al, 2014 ; Yadav et al, 2021 ). Recent evidence showed that the miR166 family plays crucial roles in response to abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in miRNA transcription or processing complexes usually have multiple effects on plant from and function, indicating that miRNAs are important to coordinate plant development. For example, the roles of HD-ZIP III-miR165/166 pathway are important in the development of vascular, meristem, and leaf polarity, and the roles of miR156/ miR172 are important in flowering time and flower pattern (D' Ario et al, 2017;Ramachandran et al, 2017;Du et al, 2020;Ma et al, 2020;Lian et al, 2021;Yadav et al, 2021). During plant development, endogenous miRNAs play an important role in gene regulation by targeting related target genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, these are accompanied by pleiotropic defects in gametophore development ( Yip et al, 2016 ), which makes inference of a role in conductive tissue development difficult. HD-ZIP III genes are regulated by the deeply conserved miRNA165/166 ( Tsuzuki et al, 2016 ; Yip et al, 2016 ; Yadav et al, 2021 ), and this suggests that a miRNA/HD-ZIP III module may broadly operate in controlling transporting tissue development.…”
Section: Evolution Of the Molecular Toolbox For Transporting Tissue D...mentioning
confidence: 99%